Utilization of Heat from The Reactor's Outlet Stream in Formaldehyde Production to Reduce Energy Usage in The Heat Exchanger - Putri, Shelma Zulaika; Chairunnisa, Shafa; Nugraha, Ario Satria (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Global production of formaldehyde has consistently risen over the past ten years, highlighting its extensive industrial applications and high demand across various sectors worldwide. However, its production continues to consume a significant amount of energy. The aim of this paper is to investigate and propose strategies for enhancing energy efficiency in formaldehyde production processes. Specifically, the study focuses on harnessing heat from the reactor's outlet stream to minimize the energy consumption associated with heat exchangers. By analyzing and optimizing the utilization of this heat source, the paper aims to contribute to sustainable manufacturing practices by reducing overall energy requirements and operational costs in formaldehyde production facilities. The process modification was simulated using Aspen HYSYS and the comparison of net-energy between the basic and the modified process is calculated using the net-energy formula. The results obtained that the Net-Energy (NE) value for both basic and modified process is 316,286,815.4 kJ/h and 125,757,792.9 kJ/h. This shows that the modified process has better energy efficiency compared to the basic process as the net-energy value zero. Therefore, this modification enhances the energy efficiency of the formaldehyde production process through methanol oxidation. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).